Penerapan Prinsip Form Follow Function Pada Pusat Penelitian Dan Budidaya Kelapa Hibrida Di Indragiri Hilir - Agustin, Rezy Kurnia; Firzal, Yohannes; Aldy, Pedia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The largest coconut plantation in Indonesiais located in peatlands of the Indragiri Hilir regency. High productivity of hybrid coconut is a source of income for farmers, communities and local revenue. Lack of facility to accommodate the needs of research and cultivation, breedingof hybrid varieties becomebackgounddesignof a Hybrid Coconut Research and Cultivation Center. This designis conducted by combining function of the facility in principle according to ‘form follow function’ and analyzed the design characteristics of Louis Henry Sullivan. The concept used in this design is optimum cubical space. Thisconcept means optimal using space to accommodate activities in buildings,which is expected to be research, education, and cultivation.The result of optimum cubical space application concept in Hybrid Coconut Research and Cultivation Center consisted zoning functions,internal space arrangements to accommodate the main functions, and on the building facades that apply the design characteristics.Keywords: Research Center, Cultivation, form follow function, Louis Henry Sullivan